Ammonia fuel proton conductor solid oxide fuel cell anode material

By adding Co-BZY catalyst to the surface of Ni-BaZr0.1Ce0.7Y0.1Yb0.1O3 anode, xCo/100-xBZY (x=10, 20 and 30)+Ni-BaZr0.1Ce0.7Y0.1Yb0.1O3 anode, the problems of poor catalytic activity and poor durability of traditional anode are solved, and the performance of highly efficient and durable ammonia fuel proton conductor solid oxide fuel cell is achieved.

CN119725575AActive Publication Date: 2025-03-28SOUTH CHINA UNIV OF TECH
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411684345.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-03-28
Estimated Expiration
2044-11-22

AI Technical Summary

Technical Problem

Traditional nickel cermet anode has poor catalytic activity for ammonia decomposition, and it is prone to coarseness at high NH3 concentrations, resulting in damage to the anode surface structure, which in turn causes the battery performance to decline rapidly.

Method used

Co-BZY catalyst was added to the surface of Ni-BaZr0.1Ce0.7Y0.1Yb0.1O3 anode to form xCo/100-xBZY (x=10, 20 and 30)+Ni-BaZr0.1Ce0.7Y0.1Yb0.1O3 anode, which improved ammonia decomposition activity and durability.

Benefits of technology

High power output and excellent durability were achieved, especially at peak power density of 700°C, 650°C, 600°C and 550°C of 1.609W cm-2, 1.387W cm-2, 0.974W cm-2, and 0.626W cm-2, respectively, and the battery showed excellent stability at a temperature of 550°C and a constant current density of 200 mA cm-2.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725575A_ABST
    Figure CN119725575A_ABST
Patent Text Reader

Abstract

The invention discloses an ammonia fuel proton conductor solid oxide fuel cell anode material. The chemical formula of the anode material is xCo / 100-xBZY + Ni-BZCYYb, the total molar weight of metal elements in Co / BZY is 100%, x is the percentage content of Co, and x is larger than or equal to 10 and smaller than or equal to 30. In order to solve the problems that in the service environment of PCFCs, low-temperature ammonia decomposition activity is poor, nitridation of a Ni phase, morphology corrosion / porosity and agglomeration coarsening of the nickel phase possibly occur after the PCFCs are exposed to high-concentration ammonia, and the performance of the battery is rapidly attenuated, the activity and durability of the Ni-BZCYYb anode are greatly improved by loading a high-activity Co / BZY catalyst layer on the Ni-BZCYYb anode. The method has the characteristics of simple process, low cost, easiness in operation and the like. The method disclosed by the invention has theoretical and practical significance for promoting the development of a stable and durable anode material for NH3-PCFCs.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of high-temperature fuel cells, and in particular relates to an anode material for an ammonia fuel proton conductor solid oxide fuel cell. Background Art

[0002] Solid oxide fuel cells are a promising technology that can efficiently generate electricity from a variety of fuels and can alleviate the growing global energy demand. They are characterized by high energy conversion efficiency, low emissions, and good fuel flexibility. Hydrogen is an excellent carbon-free energy carrier and is considered to be the preferred fuel for fuel cells, but its storage and long-distance transportation remain a major challenge. Therefore, it is necessary to further search for alternative sustainable clean fuels. Ammonia has unique physical and chemical properties, such as high hydrogen content (17.7wt.%), high energy density (4kWh kg -1 ), does not cause carbon emissions, is low-cost, is easily liquefied under mild conditions (liquefiable at room temperature and medium pressure), is easy to transport and store, and has been considered to be one of the most promising hydrogen carriers for proton conductor oxide fuel cells (PCFCs).

[0003] The ammonia decomposition reaction is an endothermic process, and the complete conversion of ammonia can be achieved at 500°C. Therefore, compared with the traditional oxygen ion-based SOFC (O-SOFC), the direct use of ammonia as fuel in the proton ceramic fuel cell PCFC (relatively low operating temperature 500-700°C) has greater application prospects. First, water vapor is generated at the cathode in the PCFC, thereby achieving high fuel utilization. In addition, since there is no oxygen ion transport in the anode or electrolyte, the potential NO x When ammonia is supplied to PCFC as fuel, the conversion process of ammonia on the anode includes a thermal catalytic process and an electrocatalytic process, which can be described by the following steps: first, NH3 is adsorbed on the anode surface, and the adsorbed NH3 is thermally decomposed into H2 and N2 under the catalysis of nickel, and then H2 is converted into protons, and then the protons are electrochemically oxidized to H2O.

[0004] However, conventional nickel metal ceramic anodes have poor catalytic activity for ammonia decomposition, and nickel metal is prone to coarsening at high NH3 concentrations, resulting in structural damage to the anode surface, which rapidly degrades battery performance. On the other hand, the poor proton conductivity of the electrolyte at lower temperatures causes PCFCs to have large ohmic resistance, leading to poor battery output power. In addition, the inefficient charge transfer rate between the electrode and electrolyte interface is also an important challenge in the development of efficient and durable proton conductor solid oxide fuels using ammonia as fuel. Summary of the invention

[0005] In view of the above-mentioned deficiencies in the prior art, the purpose of the present invention is to provide an efficient and durable ammonia fuel proton conductor solid oxide fuel cell anode material; the present invention develops a PCFC with NH3 as fuel that has high performance and excellent durability, and has the advantages of convenient and simple manufacturing and low cost. 0.1 Ce 0.7 Y 0.1 Yb 0.1 Co-BZY(Co / BaZr) was added to the surface of O3(Ni-BZCYYb) anode 0.8 Y 0.2 O 3-δ ) catalyst, forming xCo / 100-xBZY (x = 10, 20 and 30) + Ni-BaZr with high activity and excellent durability 0.1 Ce 0.7 Y 0.1 Yb 0.1 O3 anode. Under typical PCFC operating conditions, with xCo / 100-xBZY (x = 10, 20 and 30) + Ni-BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 The battery with O3 anode achieves high power output and excellent durability when generating electricity using ammonia as fuel.

[0006] The purpose of the present invention is achieved through the following technical solutions:

[0007] The first aspect of the present invention provides:

[0008] An ammonia fuel proton conductor solid oxide fuel cell anode material, the chemical formula is

[0009] xCo / 100-xBZY+Ni-BZCYYb, wherein the total molar amount of metal elements in Co / BZY is 100%, x is the percentage content of Co, and 10≤x≤30.

[0010] In one embodiment, x=10, 20 or 30.

[0011] In one embodiment, the particle size of the Co particles in the Co / BZY is 10-80 nm.

[0012] In one embodiment, the Co / BZY has a thickness of 10-20 μm.

[0013] In one embodiment, Ni-BZCYYb consists of a functional layer and a support layer, the thickness of the functional layer is 10-30 μm, and the thickness of the support layer is 700-900 μm; xCo / 100-xBZY is on the surface of the Ni-BZCYYb support layer.

[0014] In one embodiment, the Ni-BZCYYb anode is composed of two layers: an anode functional layer (thickness ~ 20 μm) and an anode support layer (thickness ~ 800 μm). The anode functional layer has finer pores and a larger surface area, providing more three-phase boundaries for electrochemical reactions. The anode support layer has larger pores and continuous channels, providing a convenient path for gas transmission.

[0015] In one embodiment, xCo / 100-xBZY is obtained by reducing xCo3O4 / 100-xBZY;

[0016] In one embodiment, the Ni-BZCYYb functional layer is obtained by reducing the NiO-BZCYYb functional layer; the mass ratio of BZCYYb to NiO in the NiO-BZCYYb functional layer is (1-3): (2-5);

[0017] In one embodiment, the Ni-BZCYYb support layer is obtained by reducing the NiO-BZCYYb support layer; the mass ratio of BZCYYb to NiO in the NiO-BZCYYb support layer is (10-20): (20-30);

[0018] In one embodiment, xCo3O4 / 100-xBZY is added on the surface of NiO-BZCYYb by screen printing.

[0019] In one embodiment, the preparation method of xCo3O4 / 100-xBZY is as follows:

[0020] Ba(NO3)2, Zr(NO3)4, Y(NO3)3 and Co(NO3)2·6H2O are added to a nitric acid aqueous solution according to a stoichiometric ratio, and citric acid is added; then ammonia water is added to adjust the pH value of the solution to 7-8; after stirring and mixing evenly, the precursor is heated and evaporated to obtain a precursor, and finally the precursor is calcined at 1100-1200°C for 6-8h to obtain xCo3O4 / 100-xBZY.

[0021] In one embodiment, the molar ratio of the total amount of metal ions to citric acid is 1:(2-3).

[0022] In one embodiment, the preparation of the Co / BZY catalyst comprises the following steps:

[0023] Synthesis of Co3O4 / BaZr with different ratios by citrate method 0.8 Y 0.2 O 3-δ(Co / BZY) catalyst powder. First, add a certain amount of dilute nitric acid (about 10 ml) to about 200 ml of deionized water solution, and add Ba(NO3)2, Zr(NO3)4, Y(NO3)3 and Co(NO3)2·6H2O in the stoichiometric ratio of 0.01 mol Co / BZY to the nitric acid aqueous solution (concentration is about 3wt%) in turn, and add a certain amount of citric acid (CA) (the molar ratio of metal ion: CA is 1:2). Then add an appropriate amount of ammonia water to adjust the pH value of the solution to 7-8. After the solution is heated and stirred to be fully mixed (about 6 hours), pour the solution into a ceramic evaporating dish and continue heating it until it is completely heated and transformed into a gel, then continue to heat the gel to obtain an ash-like precursor, and finally Co3O4 / BaZr 0.8 Y 0.2 O 3-δ The precursor powder was calcined at 1100℃ for 6h to obtain Co3O4 / BaZr 0.8 Y 0.2 O 3-δ Powder. Then synthesize the ratio of 10Co3O4 / 90BaZr 0.8 Y 0.2 O 3-δ 、20Co3O4 / 80BaZr 0.8 Y 0.2 O 3-δ and 30Co3O4 / 70BaZr 0.8 Y 0.2 O 3-δ The catalyst powders of xCo / 100-xBZY (x=10, 20 and 30) were obtained by reducing the Co3O4 / BZY catalyst powders of different ratios in H2 at 700°C for 2h.

[0024] The second aspect of the present invention provides:

[0025] An ammonia fuel proton conductor solid oxide fuel cell comprises a proton conductor electrolyte and an anode and a cathode located on both sides of the proton conductor electrolyte, wherein the anode is the ammonia fuel proton conductor solid oxide fuel cell anode material.

[0026] In one embodiment, the proton conductor electrolyte is BZCYYb, and the thickness of the proton conductor electrolyte is 5-10 μm; the cathode is PBSCF, and the thickness of the cathode is 10-20 μm.

[0027] In one embodiment, the fuel cell is xCo / 100-xBZY (x=10, 20 and 30)

[0028] +Ni-BZCYYb|BZCYYb|PBSCF.

[0029] In one embodiment, the fuel cell is a proton conductor oxide fuel cell using ammonia as fuel.

[0030] In one embodiment, the anode material 20Co / 80BZY+Ni-BZCYYb is used to improve the ammonia decomposition activity and long-term stability of the anode.

[0031] In one embodiment, the configuration is xCo / 100-xBZY (x=10, 20 and 30)

[0032] +Ni-BZCYYb|BZCYYb|PBSCF proton conductor solid oxide fuel cell, the structure of which includes a proton conductor electrolyte BZCYYb, and an xCo / 100-xBZY (x=10, 20 and 30)+Ni-BZCYYb anode and a PBSCF cathode located on both sides of the proton conductor electrolyte;

[0033] In one embodiment, the xCo / 100-xBZY (x=10, 20 and 30)+Ni-BZCYYb anode refers to a Ni-BaZr with a Co-BZY catalyst layer. 0.1 Ce 0.7 Y 0.1 Yb 0.1 O3(Ni-BZCYYb) anode.

[0034] In one embodiment, the material of the proton conductor electrolyte is BZCYYb, whose chemical formula is BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O3.

[0035] In one embodiment, the proton conductor cathode is a PBSCF cathode, wherein the chemical formula of PBSCF is PrBa 0.5 Sr 0.5 Co 1.5 Fe 0.5 O 5+δ , where δ represents the oxygen vacancy content.

[0036] The third aspect of the present invention provides:

[0037] The above configuration is xCo / 100-xBZY (x=10, 20 and 30) + Ni-BZCYYb|BZCYYb|PBSCF anode support proton conductor solid oxide fuel cell preparation method, is first by co-casting and co-sintering method to prepare NiO-BZCYYb anode support half-cell (including BZCYYb electrolyte layer, NiO-BZCYYb anode support layer and NiO-BZCYYb anode functional layer). PBSCF cathode slurry is screen-printed on the electrolyte surface of the half-cell, and then placed in a high-temperature muffle furnace at 950 ° C. calcined for 2h to obtain the desired NiO-BZCYYb|BZCYYb|PBSC single cell. Then, the xCo3O4 / 100-xBZY (x=10, 20 and 30) catalytic layer was added to the NiO-BZCYYb anode surface by screen printing to obtain xCo3O4 / 100-xBZY (x=10, 20 and 30) + NiO-BZCYYb | BZCYYb | PBSCF single cell, and then reduced to obtain xCo / 100-xBZY (x=10, 20 and 30) + Ni-BZCYYb | BZCYYb | PBSCF single cell.

[0038] In one embodiment, the co-casting and co-sintering method of the NiO-BZCYYb anode support half-cell is as follows: first, the electrolyte slurry, the anode functional layer slurry and the anode support slurry are sequentially cast on the polymer film, and then dried in air for 12 hours; after drying, a 15 cm diameter grinder is used to knock it into about 100 small pieces, and then the pieces are placed in a high-temperature muffle furnace and calcined at 600°C for 2 hours (this process is a degreasing process). During the degreasing process, a slow heating rate is used to remove the organic components in the sheet. Finally, the degreased sheet is placed in a high-temperature muffle furnace and calcined at 1450°C for 5 hours to obtain the desired Ni-BZCYYb anode support half-cell.

[0039] In one embodiment, the preparation method of the PBSCF cathode slurry is as follows: weigh 1 g of PBSCF cathode powder, 0.004 g of PVb, and 0.076 g of pineneol, pour them into a mortar and grind them for 1-3 hours to obtain the desired cathode slurry.

[0040] In one embodiment, the effective area of ​​the PBSCF cathode screen printing is 0.2826 cm 2 .

[0041] A fourth aspect of the present invention provides:

[0042] The above-mentioned method for preparing the PBSCF cathode powder is to adopt a sol-gel method.

[0043] In one embodiment, the sol-gel method comprises the following steps:

[0044] According to the stoichiometric ratio, Pr(NO3) 3, Ba(NO3)2, Sr(NO3)2, Co(NO3)2·6H2O, Fe(NO3)3·9H2O are added into deionized water to dissolve and heat and stir evenly; glycine and citric acid monohydrate are added, and the water is evaporated under heating and stirring conditions to obtain a gel-like substance; the gel-like substance is placed in an oven for drying to obtain a cathode material precursor, and then the precursor is placed in a muffle furnace for roasting to obtain the desired battery cathode material.

[0045] In one embodiment, the total molar ratio of glycine and citric acid to Pr, Ba, Sr, Co, Co, Fe is 0.75:0.75:1.

[0046] In one embodiment, the drying process is carried out at 250° C. for 2 hours.

[0047] In one embodiment, the calcination parameters are 900° C. for 2 hours.

[0048] A fifth aspect of the present invention provides:

[0049] The above-mentioned method for preparing BZCYYb powder is to adopt a solid phase method.

[0050] In one embodiment, the solid phase method comprises the following steps: dissolving high-purity barium carbonate, zirconium oxide, cerium oxide, ytterbium oxide and yttrium oxide powders in ethanol in a stoichiometric ratio and ball milling for 24 hours to mix evenly, placing the mixed solution in an oven to dry to obtain a dry powder, and then pressing the dry powder into tablets, placing it in a muffle furnace and calcining it at 1100°C for 12 hours. Then, the calcined powder is added to ethanol and high-energy ball milled again for 4 hours, dried and pressed into tablets, and then placed in a muffle furnace and calcined at 1100°C for 12 hours to obtain a pure perovskite phase. After adding the obtained powder to ethanol and high-energy ball milling for 4 hours, the desired BZCYYb powder is obtained.

[0051] In one embodiment, tableting uses a pressure of 10 MPa.

[0052] A sixth aspect of the present invention provides:

[0053] The above configuration is a current collection method for xCo / 100-xBZY (x=10, 20 and 30)+Ni-BZCYYb|BZCYYb|PBSCF proton conductor fuel cells.

[0054] In one embodiment, the current collection method of the proton conductor fuel cell is to connect the electrode surface with silver wires for current collection using silver paste (DAD-87, purchased from Shanghai Synthetic Resin Research Institute).

[0055] The present invention has the following beneficial effects:

[0056] The anode of the present invention is a Co-BZY catalyst with different Co contents added to the surface of the Ni-BZCYYb anode to form a Co-modified xCo / 100-xBZY (x=10, 20 and 30)+Ni-BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O3(Co / BZY+Ni-BZCYYb) anode.

[0057] The proton conductor solid oxide fuel cell configured as 20Co / 80BZY+Ni-BZCYYb|BZCYYb|PBSCF has excellent electrochemical performance when ammonia is used as fuel gas, and the peak power density at 700°C, 650°C, 600°C and 550°C is 1.609W cm -2 , 1.387 W cm -2 , 0.974 W cm -2 , and 0.626 W cm -2 At 550°C and 200 mA cm -2 At a constant current density of 20Co / 80BZY+Ni with ammonia as fuel

[0058] -BZCYYb|BZCYYb|PBSCF battery showed excellent stability. In the long-term operation of 100h, the battery decay rate per hour was only 0.047V h -1 .

[0059] The 20Co / 80BZY+Ni-BZCYYb|BZCYYb|PBSCF proton conductor solid oxide fuel cell of the present invention also has excellent electrochemical performance when hydrogen is used as fuel gas. BRIEF DESCRIPTION OF THE DRAWINGS

[0060] Figure 1 This is a SEM image of the reduced 20Co / 80BZY catalyst according to the present invention;

[0061] Figure 2 The SEM image (a) of the 20Co / 80BZY+Ni-BZCYYb anode of the present invention; the SEM image (b) of the anode functional layer; and the SEM images (c and d) of the anode support layer.

[0062] Figure 3 TEM image (a) of the 20Co / 80BZY catalyst of the present invention; HRTEM image (b) of the BZY phase in the 20Co / 80BZY catalyst; HRTEM image (c) of the Co phase in the 20Co / 80BZY catalyst; FFT image (d) corresponding to the HRTEM image of the BZY phase in the 20Co / 80BZY catalyst; FFT image (e) corresponding to the HRTEM image of the Co phase in the 20Co / 80BZY catalyst;

[0063] Figure 4 It is an XRD comparison diagram of the Co3O4-BZY after reduction and the 20Co3O4 / 80BZY and NiO-BZCYYb powders after uniform reduction in a 1:1 ratio;

[0064] Figure 5 A curve diagram showing changes in polarization resistance and ohmic resistance of a proton conductor solid oxide fuel cell configured as Ni-BZCYYb|BZCYYb|PBSCF and xCo / 100-xBZY (x=10, 20 and 30)+Ni-BZCYYb|BZCYYb|PBSCF with temperature when generating electricity using ammonia as fuel gas;

[0065] Figure 6 The present invention relates to an IVP curve diagram of a proton conductor solid oxide fuel cell configured as Ni-BZCYYb|BZCYYb|PBSCF tested in the range of 550-700° C. when using ammonia and hydrogen as fuel gas for power generation;

[0066] Figure 7 The present invention relates to an impedance diagram of a proton conductor solid oxide fuel cell configured as Ni-BZCYYb|BZCYYb|PBSCF tested at a temperature of 550 to 700° C. when using ammonia and hydrogen as fuel gases to generate electricity;

[0067] Figure 8 The IVP curve diagram of the proton conductor solid oxide fuel cell configured as 20Co / 80BZY+Ni-BZCYYb|BZCYYb|PBSCF of the present invention tested in the range of 550-700°C when using ammonia and hydrogen as fuel gas for power generation;

[0068] Fig. 9 The present invention relates to an impedance diagram of a proton conductor solid oxide fuel cell configured as 20Co / 80BZY+Ni-BZCYYb|BZCYYb|PBSCF tested at a temperature of 550-700°C when using ammonia and hydrogen as fuel gases for power generation;

[0069] Fig.10The configuration of the present invention is Ni-BZCYYb|BZCYYb|PBSCF and 20Co / 80BZY+Ni

[0070] -BZCYYb|BZCYYb|PBSCF's proton conductor solid oxide fuel cell, single cell stability diagram tested at 550°C when generating electricity using ammonia as fuel gas. DETAILED DESCRIPTION

[0071] The present invention is further described in detail below in conjunction with examples and drawings, but the embodiments of the present invention are not limited thereto.

[0072] The anode material and proton conductor solid oxide fuel cell involved in the present invention include but are not limited to the materials in the following embodiments, and the optimization method and preparation method involved include but are not limited to the methods in the following embodiments. Any modification or equivalent replacement of the technical solution of the present invention without departing from the spirit and scope of the technical solution of the invention shall be included in the protection scope of the present invention.

[0073] Example 1

[0074] This embodiment provides a method for preparing an anode catalyst layer precursor material xCo3O4 / 100-xBZY (x=10, 20 and 30) of a proton conductor fuel cell, and the specific steps are as follows:

[0075] (1) Ba(NO3)2, Zr(NO3)4, Y(NO3)3 and Co(NO3)2·6H2O were weighed in accordance with the stoichiometric ratio of Co3O4 / BZY and added sequentially into an aqueous nitric acid solution (concentration of about 3 wt%), and the total concentration of metal ions was 0.05 M.

[0076] (2) Add a certain amount of citric acid (CA) (the molar ratio of metal ion:CA is 1:2).

[0077] (3) Then add appropriate amount of ammonia water to adjust the pH value of the solution to 7-8.

[0078] (4) After the solution is fully heated and mixed at 180°C in a magnetic stirrer (about 6 hours), the solution is poured into a ceramic evaporating dish and heated at 250°C until it is completely heated and transformed into a gel state. The gel is then heated to obtain an ash precursor. Finally, the ash precursor powder is calcined at 1100°C for 6 hours to obtain the precursor material Co3O4 / BaZr 0.8 Y 0.2 O 3-δ .

[0079] Example 2

[0080] This embodiment provides a method for preparing a xCo3O4 / 100-xBZY (x=10, 20 and 30)+Ni-BZCYYb|BZCYYb|PBSCF proton conductor solid oxide fuel cell, and the specific steps are as follows:

[0081] (1) Preparation of BZCYYb(BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O3) Powder, using solid phase method, as follows:

[0082] High-purity barium carbonate, zirconium oxide, cerium oxide, ytterbium oxide and yttrium oxide powders were dissolved in ethanol in a stoichiometric ratio and ball-milled for 24 hours to mix evenly. The mixed solution was placed in an oven at 70°C to obtain a dry powder, and then the dry powder was pressed into a tablet at 10Mpa and calcined at 1100°C in a muffle furnace for 12 hours. The calcined powder was then added to ethanol and high-energy ball-milled again for 4 hours. After drying, it was pressed into small discs using a tabletting mold with a diameter of about 13mm. The tablets were then placed in a muffle furnace and calcined at 1100°C for 12 hours to obtain a pure perovskite phase. The obtained powder was added to ethanol and high-energy ball-milled for 4 hours to obtain the desired BZCYYb powder.

[0083] (2) Preparation of PBSCF (PrBa 0.5 Sr 0.5 Co 1.5 Fe 0.5 O 5+δ ) cathode powder, using the sol-gel method, as follows:

[0084] According to the stoichiometric ratio, Pr(NO3)3, Ba(NO3)2, Sr(NO3)2, Co(NO3)2·6H2O and Fe(NO3)3·9H2O are added to deionized water in turn to dissolve and heat and stir evenly; glycine and citric acid monohydrate are added (the total molar ratio of glycine and citric acid to Pr, Ba, Sr, Co, Co and Fe is 0.75:0.75:1), and the water is evaporated under heating and stirring to obtain a gel-like substance; the gel-like substance is placed in an oven to dry (treated at 250°C for 2h) to obtain a cathode material precursor, and the precursor is then placed in a muffle furnace for calcination (calcination at 900°C for 2h) to obtain the required battery cathode PBSCF material.

[0085] (3) First, a NiO-BZCYYb anode support half-cell (including a BZCYYb electrolyte layer, a NiO-BZCYYb anode support layer and a NiO-BZCYYb anode functional layer) was prepared by co-casting and co-sintering as follows:

[0086] Electrolyte BZCYYb slurry (5g BZCYYb mixed with 3g ethanol, 0.5g plasticizer and 1g PVB binder), anode functional layer slurry (2g BZCYYb, 3g NiO mixed with 3g ethanol, 0.5g plasticizer and 1g PVB binder) and anode support slurry (15g BZCYYb, 25g NiO mixed with organic solvent 12g ethanol, 2.5g plasticizer and 5g PVB binder) were cast on the polymer film in sequence with a thickness of about 8μm, 20μm and 800μm, and then dried in air for 12h; after drying, a 15cm diameter grinder was used to knock it into about 100 small pieces, and then the pieces were placed in a high-temperature muffle furnace and calcined at 600℃ for 2h (this process is the degreasing process). During the degreasing process, a slow heating rate (2℃ / h) was used to remove the organic components in the piece. Finally, the degreased sheet was placed in a high-temperature muffle furnace and calcined at 1450°C for 5 hours to obtain the desired NiO-BZCYYb anode-supported half-cell.

[0087] (4) The preparation method of PBSCF cathode slurry is as follows: weigh 1 g PBSCF cathode powder, 0.004 g PVb, and 0.076 g pineol, pour them into a mortar and grind them for 1-3 h to obtain the required cathode slurry.

[0088] The PBSCF cathode slurry was screen-printed on the electrolyte surface of the half-cell (effective area 0.2826 cm 2 , thickness is about 10 μm), and then placed in a high-temperature muffle furnace and calcined at 950 ° C for 2 h to obtain the required NiO-BZCYYb|BZCYYb|PBSCF single cell.

[0089] (5) Then, the xCo3O4 / 100-xBZY (x=10, 20 and 30) catalyst layer precursor material was added to the NiO-BZCYYb anode surface of the above-mentioned single cell (thickness is about 10 μm) by screen printing, specifically: 1 g of xCo3O4 / 100-xBZY (x=10, 20 and 30) catalyst layer precursor material powder, 0.004 g of PVb, and 0.076 g of pine alcohol were weighed into a mortar and ground for 1-3 h to obtain the required catalyst layer slurry; xCo3O4 / 100-xBZY (x=10, 20 and 30) was obtained.

[0090] +NiO-BZCYYb|BZCYYb|PBSCF single battery.

[0091] Example 3

[0092] This embodiment provides a test of the electrochemical performance of a xCo3O4 / 100-xBZY (x=10, 20 and 30)+NiO-BZCYYb|BZCYYb|PBSCF proton conductor solid oxide fuel cell, which specifically includes the following specific steps:

[0093] (1) Before the electrochemical test, the electrode surface was partially connected to the silver mesh using silver paste (DAD-87, purchased from Shanghai Synthetic Resin Research Institute) for current collection.

[0094] (2) Use ceramic sealant to seal the battery.

[0095] (3) The single cell is heated to 700°C in an air environment.

[0096] (4) Pass nitrogen gas (flow rate: 20 ml / min) for 5 min to exhaust all the air in the tube.

[0097] (5) After the air in the tube is purged, the nitrogen is cut into humidified H2 (~3% H2O) (flow rate of 30 ml / min) for reducing the anode, and the cathode is exposed to the ambient air.

[0098] (6) When H2 is introduced into the anode for about 20 min (flow rate is 20 ml / min), the battery is observed to have a stable OCV.

[0099] (7) The hydrogen at the anode was then cut into NH3 (flow rate of 20 ml / min), and the open circuit voltage (OCV), current-voltage (IV), and impedance spectrum characteristics of the battery were tested in an ammonia atmosphere using an electrochemical workstation (AMETEK PARSTAT MC) at a test temperature of 550°C to 700°C.

[0100] Characterization results

[0101] 1. Electron microscopy characterization

[0102] Figure 1 This is the powder morphology of the synthesized 20Co3O4 / 80BZY catalyst after reduction in H2. It can be seen that the particle-shaped Co phase is distributed in the gaps of the BZY phase.

[0103] Electron microscopy images of the Ni-BZCYYb anode layers of the 20Co / 80BZY+Ni-BZCYYb|BZCYYb|PBSCF proton conductor solid oxide fuel cell obtained after reduction are shown in Figure 2 , we can see that the anode support of the battery PCFC anode Ni-BZCYYb consists of two layers ( Figure 2a) in Fig. 1: anode functional layer (AFL, ~20 μm) and anode support layer (ASL, ~800 μm). The anode functional layer has finer pores and larger surface area (mainly due to the reduction of NiO), providing more three-phase boundaries for electrochemical reactions, such as Figure 2 In contrast, the anode support layer has larger pores and continuous channels (mainly due to the removal of pore formers), providing convenient pathways for gas transport, such as Figure 2 c and Figure 2 In d.

[0104] Figure 3 The transmission electron microscopy (TEM) image and energy dispersive spectroscopy (EDS) elemental map of the 20Co / 80BZY catalyst obtained after reduction were used to analyze the element distribution and composition of the catalyst. Figure 3 a and high-resolution TEM ( Figure 3 The results in b) show that the catalyst consists of two phases, Co and BZY, and the elements Ba, Zr, Y and O are uniformly present in the BZY phase of the catalyst. The Co phase with a particle size of about 10-80nm is distributed in the gaps of the BZY phase. Figure 3 As shown in Figures b and d, the interplanar spacing is about 0.297 nm, corresponding to the (110) plane of BZY (PDF#70-3667). Figure 3 As shown in c and e, the interplanar spacing is about 0.192 nm, corresponding to the (101) plane of Co (PDF#89-4307). This indicates that the 20Co / 80BZY catalyst after hydrogen treatment is composed of two phases: Co phase and BZY phase.

[0105] 2. XRD characterization

[0106] Figure 4 The XRD patterns of xCo / 100-xBZY (x=10, 20 and 30) and 20Co / 80BZY+Ni-BZCYYb anode 1:1 mixture obtained after reduction. The results show that the catalyst is composed of two phases, Co and BZY. Figure 4 As shown in a, the peaks at 31.4° and 65.4° are characteristic peaks of Co (PDF#73-1701). With the increase of Co content, the intensity of Co peak increases. After the synthesized xCo3O4 / 1-xBZY (x=10, 20 and 30) catalyst powders with different ratios were reduced in 700℃ H2 for 2h, the Co3O4 phase was reduced to the Co phase. After 20Co3O4 / 80BZY and NiO-BZCYYb powders were mixed in a ratio of 1:1 and reduced in 700℃ H2 for 2h, the XRD pattern is shown in Figure 4As shown in a and b (red lines), characteristic peaks of Ni, BaZrO3, and Co were detected, indicating that under the test conditions, the catalytic layer material and the anode had no phase reaction and had good chemical compatibility.

[0107] 3. Output power characterization

[0108] Figure 5 The electrochemical impedance spectroscopy of the symmetrical anode battery system. The xCo3O4 / 100-xBZY (x = 10, 20 and 30) powder was mechanically mixed with organic additives (α-pinene alcohol and ethyl cellulose) and ground into Co3O4 / BZY catalyst layer slurry in a mortar. 2 ) First, apply NiO-BZCYYb slurry (prepared as above), and then screen print Co3O4 / BZY catalyst layer slurry on both sides of the BZCYYb electrolyte sheet (the anode active area is 0.2826 cm 2 ), and then the symmetrical battery was placed in a test furnace under a hydrogen atmosphere at 700° C. for reduction for 2 h to form a porous anode catalyst layer, and then switched to an ammonia atmosphere for AC impedance testing.

[0109] For the blank Ni-BZCYYb anode, at 550, 600, 650 and 700 °C, its R p The values ​​are 51.55, 17.87, 5.67 and 2.28Ωcm respectively 2 (See Figure 5 a in Figure 1). It is significantly higher than the Ni / BZCYYb anode with xCo / 100-xBZY (x = 10, 20 and 30) catalyst layer (see Figure 2). Figure 5 b, c and d in Figure 1). With the increase of Co content in the ratio of xCo / 100-xBZY, (x = 10, 20 and 30), the symmetrical battery R p The anode with 20Co / 80BZY catalyst layer has a R p The values ​​are 3.82, 1.82, 1.01 and 0.65Ωcm respectively 2 , its R p The values ​​are smaller than those of the blank anode at each temperature, indicating that the addition of 20Co / 80BZY catalytic layer can accelerate the anode electrochemical reaction and improve the electrochemical performance of Ni / BZCYYb anode under NH3 conditions.

[0110] Figure 6 Ni-BZCYYb(BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1O3) as the anode, and the prepared single cell (Ni-BZCYYb|BZCYYb|PBSCF) was subjected to IVP test in the range of 550-700℃. From the test results, it can be seen that when Ni-BZCYYb|BZCYYb|PBSCF is fueled by ammonia at 550, 600, 650 and 700℃, the maximum output power reaches 0.493, 0.773, 1.095 and 1.452Wcm -2 At 700℃, when hydrogen is used as fuel, the maximum output power reaches 1.80Wcm -2 .

[0111] Figure 7 In order to adopt Ni-BZCYYb(BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 Electrochemical impedance diagram of a single cell (Ni-BZCYYb|BZCYYb|PBSCF) with O3) as the anode. When NH3 is used as the fuel, the polarization resistance (R p ) values ​​at 700, 650, 600 and 550℃ are 0.065, 0.119, 0.277 and 0.618Ωcm respectively 2 At 700℃, when hydrogen is used as fuel, R p 0.81Ωcm 2 .

[0112] Figure 8 Based on 20Co / 80BZY+Ni-BZCYYb(BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O3) as the anode, the prepared single cell (20Co / 80BZY+Ni-BZCYYb|BZCYYb|PBSCF) was subjected to IVP test in the range of 550-700℃. From the test results, it can be seen that the maximum output power of 20Co / 80BZY+Ni-BZCYYb|BZCYYb|PBSCF at 550, 600, 650 and 700℃, when ammonia is used as fuel, reaches 0.626, 0.974, 1.387 and 1.609Wcm -2 At 700°C, when hydrogen is used as fuel, the maximum output power reaches 2.147Wcm -2 .

[0113] Fig. 9 20Co / 80BZY+Ni-BZCYYb(BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1Electrochemical impedance spectroscopy of a single cell (20Co / 80BZY+Ni-BZCYYb|BZCYYb|PBSCF) with 20Co / 80BZY catalyst layer as anode. p The values ​​decreased to 0.037, 0.086, 0.200 and 0.463Ωcm at 700, 650, 600 and 550℃, respectively. 2 , at 700℃, when hydrogen is used as fuel, R p 0.027Ωcm 2 The results show that the 20Co / 80BZY catalyst layer can accelerate the anode reaction and reduce the polarization resistance, thereby improving the battery performance.

[0114] 4. Single cell stability characterization

[0115] Fig.10 The single cell (20Co / 80BZY+Ni-BZCYYb) is prepared with 20Co / 80BZY+Ni

[0116] -BZCYYb|BZCYYb|PBSCF), stability diagram of a single cell tested at 550°C. In the figure, 200A cm -2 Under load current, there was no obvious voltage drop (0.047V / h) for 100 hours, and the voltage of Ni-BZCYYb|BZCYYb|PBSCF battery dropped significantly (0.169V / h). It can be seen that 20Co / 80BZY+Ni-BZCYYb as anode material maintains excellent stability in ammonia atmosphere, providing a guarantee for commercial progress.

Claims

1. An ammonia fuel proton conductor solid oxide fuel cell anode material, characterized in that: The chemical formula is xCo / 100-xBZY+Ni-BZCYYb, wherein the total molar amount of metal elements in Co / BZY is 100%, x is the percentage content of Co, and 10≤x≤30.

2. The ammonia fuel proton conductor solid oxide fuel cell anode material according to claim 1, characterized in that: x=10, 20 or 30.

3. The ammonia fuel proton conductor solid oxide fuel cell anode material according to claim 1, characterized in that: The particle size of Co particles in Co / BZY is 10-80 nm; the thickness of Co / BZY is 10-20 μm.

4. The ammonia fuel proton conductor solid oxide fuel cell anode material according to claim 1, characterized in that: Ni-BZCYYb consists of a functional layer and a supporting layer. The thickness of the functional layer is 10-30 μm, and the thickness of the supporting layer is 700-900 μm. xCo / 100-xBZY is on the surface of the Ni-BZCYYb supporting layer.

5. The ammonia fuel proton conductor solid oxide fuel cell anode material according to claim 1, characterized in that: xCo / 100-xBZY is obtained by reducing xCo3O4 / 100-xBZY; The Ni-BZCYYb functional layer is obtained by reducing the NiO-BZCYYb functional layer; the mass ratio of BZCYYb to NiO in the NiO-BZCYYb functional layer is (1-3):(2-5); The Ni-BZCYYb support layer is obtained by reducing the NiO-BZCYYb support layer; the mass ratio of BZCYYb to NiO in the NiO-BZCYYb support layer is (10-20): (20-30); xCo3O4 / 100-xBZY was added on the surface of NiO-BZCYYb by screen printing.

6. The ammonia fuel proton conductor solid oxide fuel cell anode material according to claim 5, characterized in that: The preparation method of xCo3O4 / 100-xBZY is as follows: Ba(NO3)2, Zr(NO3)4, Y(NO3)3 and Co(NO3)2·6H2O are added to a nitric acid aqueous solution according to a stoichiometric ratio, and citric acid is added; then ammonia water is added to adjust the pH value of the solution to 7-8; after stirring and mixing evenly, the precursor is heated and evaporated to obtain a precursor, and finally the precursor is calcined at 1100-1200°C for 6-8h to obtain xCo3O4 / 100-xBZY.

7. The ammonia fuel proton conductor solid oxide fuel cell anode material according to claim 6, characterized in that: The molar ratio of the total amount of metal ions to citric acid is 1:(2-3).

8. An ammonia fuel proton conductor solid oxide fuel cell, characterized in that: The invention comprises a proton conductor electrolyte and an anode and a cathode located on both sides of the proton conductor electrolyte, wherein the anode is the ammonia fuel proton conductor solid oxide fuel cell anode material according to any one of claims 1 to 7.

9. The ammonia fuel proton conductor solid oxide fuel cell according to claim 8, characterized in that: The proton conductor electrolyte is BZCYYb, and the thickness of the proton conductor electrolyte is 5-10 μm; the cathode is PBSCF, and the thickness of the cathode is 10-20 μm.

10. The ammonia fuel proton conductor solid oxide fuel cell according to claim 8, characterized in that: The ammonia fuel proton conductor solid oxide fuel cell uses ammonia as fuel.

Citation Information

Patent Citations

  • Preparation method of fuel cell nano electrode material

    CN105047949A

  • Proton conductor fuel cell cathode material with B-site defect, electrolyte and preparation method thereof

    CN110429288A

  • Proton type solid oxide fuel cell cathode material and application

    CN111224110A

  • Method for preparing ceramic composite membrane of proton conduction type solid oxide pool through water-based tape casting

    CN114044673A

  • Proton type ceramic fuel cell of direct ammonia fuel and preparation method of proton type ceramic fuel cell

    CN115020717A